A Conceptual Model for Understanding Academic Physicians' Performances of Identity: Findings From the University of Utah. (October 2018) - Chow, Candace J.; Byington, Carrie L.; Olson, Lenora M.; Ramirez, Karl Paulo Garcia; Zeng, Shiya; López, Ana María
Abstract : Purpose: To explore how academic physicians perform social and professional identities and how their personal experiences inform professional identity formation. Method: Semistructured interviews and observations were conducted with 25 academic physicians of diverse gender and racial/ethnic backgrounds at the University of Utah School of Medicine from 2015 to 2016. Interviews explored the domains of social identity, professional identity, and relationships with patients and colleagues. Patient interactions were observed. Interviews and observations were audio-recorded, transcribed, and analyzed using grounded theory. Results: Three major themes emerged: Physicians' descriptions of identity differed based on social identities, as women and racially/ethnically minoritized participants linked their gender and racial/ethnic identities, respectively, to their professional roles more than men and white, non-Latino/a participants; physicians' descriptions of professional practice differed based on social identities, as participants who associated professional practices with personal experiences often drew from events connected to their minoritized identities; and physicians' interactions with patients corresponded to their self-described actions. Conclusions: Professional identity formation is an ongoing process, and the negotiation of personal experiences is integral to this process. This negotiation may be more complex for physicians with minoritized identities. Implications for medical education include providing students, trainees, and practicing physicians with intentional opportunities for reflection and instruction on connecting personal experiences and professional practice.